Comparative assessment of real estate market development strategies in countries with economies in transition - Adamov, Alexander (Global Prosperity, 2025)
Abstract. The article is devoted to a comparative analysis of real estate market development strategies in countries with economies in transition, with an emphasis on their institutional, economic, legal and investment features. The study reveals the specifics of the functioning of real estate markets, determined by historical, political and socio-economic factors, and offers methodological approaches to assessing their development. The aim of the article is to assess the effectiveness of real estate market development strategies in countries with economies in transition by analyzing their institutional, economic, legal and investment aspects, as well as identifying optimal management models that take into account national characteristics and global trends. The study is based on a comparative analysis of five countries (Poland, Hungary, Georgia, Kazakhstan, Ukraine) using a systemic approach, including market trend analysis, regression modeling, geographic information systems, assessment of the legal environment and investment attractiveness. Statistical data, reports of international organizations (Statista, Global Property Guide), as well as scenario planning and institutional analysis methods to assess the effectiveness of regulatory and financial instruments. It is found that the success of strategies depends on the level of institutional maturity and transparency. Poland achieved stability through privatization and land law reforms, Hungary through mortgage liberalization and social programs, Georgia precisely through deregulation, Kazakhstan through state programs and digitalization, while Ukraine faces legal uncertainty. It is found that an integrated approach that combines economic efficiency, social responsibility and environmental sustainability is key to the sustainable development of markets. Further research should focus on developing adaptive strategic management models, integrating digital technologies, and assessing the impact of global climatic and geopolitical factors on real estate markets. Particular attention should be paid to improving socially oriented instruments, revitalizing depressed regions, and harmonizing national policies with international sustainable development standards.